A comparative genomic analysis at the chromosomal-level reveals evolutionary patterns of aphid chromosomes - Chen Huang; Bingru Ji; Zhaohui Shi; Jiangyue Wang; Jiaqing Yuan; Peng Yang; Xiao Xu; Haohao Jing; Lulu Xu; Jing Fu; Le Zhao; Yandong Ren; et al. (Communications Biology)
Abstract Genomic rearrangements are primary drivers of evolution, promoting biodiversity. Aphids, an agricultural pest with high species diversity, exhibit rapid chromosomal evolution and diverse karyotypes. These variations have been attributed to their unique holocentric chromosomes and parthenogenesis, though this hypothesis has faced scrutiny. In this study, we generated a chromosomal-level reference genome assembly of the celery aphid (Semiaphis heraclei) and conducted comparative genomic analysis, revealing varying chromosomal evolution rates among aphid lineages, positively correlating with species diversity. Aphid X chromosomes have undergone frequent intra-chromosomal recombination, while autosomes show accelerated inter-chromosomal recombination. Moreover, considering both inter- and intra-chromosomal rearrangements, the increased autosomal rearrangement rates may be common across the Aphidomorpha. We identified that the expansion of DNA transposable elements and short interspersed nuclear elements (SINEs), coupled with gene loss and duplication associated with karyotypic instability (such as RIF1, BRD8, DMC1, and TERT), may play crucial roles in aphid chromosomal evolution. Additionally, our analysis revealed that the mutation and expansion of detoxification gene families in S. heraclei may be a key factor in adapting to host plant chemical defenses. Our results provide new insights into chromosomal evolutionary patterns and detoxification gene families evolution in aphids, aiding the understanding of species diversity and adaptive evolution.